2018
DOI: 10.5014/ajot.2018.025114
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Somatosensory Impairment on Participation After Stroke

Abstract: OBJECTIVE. Our objective was to determine the effect of loss of body sensation on activity participation in stroke survivors. METHOD. Participants (N = 268) were assessed at hospital admission for somatosensory and motor impairment using the National Institutes of Health Stroke Scale. Participation was assessed using the Activity Card Sort (ACS) in the postacute phase. Between-group differences in activity participation were analyzed for participants with and without somatosensory impairment and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
62
1
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(83 citation statements)
references
References 32 publications
3
62
1
3
Order By: Relevance
“…Somatosensory and cognitive impairment, cardiorespiratory disability following stroke, are associated with reduced activity partic-ipation. [18][19][20] Winovich et al observed that markers of physical function-walking speed and grip strength-were consistently associated with survival and recovery after ischemic stroke. 21 Leijon et al showed that the symptoms and signs indicate that the crucial factor for the development of CPSP is a lesion affecting the spino-thalamo-cortical pathway important for temperature and pain sensibility.…”
Section: Discussionmentioning
confidence: 99%
“…Somatosensory and cognitive impairment, cardiorespiratory disability following stroke, are associated with reduced activity partic-ipation. [18][19][20] Winovich et al observed that markers of physical function-walking speed and grip strength-were consistently associated with survival and recovery after ischemic stroke. 21 Leijon et al showed that the symptoms and signs indicate that the crucial factor for the development of CPSP is a lesion affecting the spino-thalamo-cortical pathway important for temperature and pain sensibility.…”
Section: Discussionmentioning
confidence: 99%
“…With the continuation of the treatment, there was improved flexibility and increased score in Oxford scale (2 to 5), showing that psychomotor practice promotes reeducation by means of adjustments in tonic activity, bettering motor control [14]. This evolution is also due to neuroplasticity phenomenon, which occurs due to the brain's ability to learn and change, because the cells of other areas that were not affected by the stroke may assume certain functions once performed by affected cells [15].…”
Section: Discussionmentioning
confidence: 98%
“…Ludic-activities-based therapeutic suitcase for rehabilitation of people with stroke Learning with playfulness is more efficient at all ages because playful activities arouse interest in the individual and has real daily components [13,14].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Obgleich somit die Evidenzlage für ein sensorisches Üben insgesamt auf der Basis systematischer Übersichtsarbeiten nach wie vor als nur gering eingeschätzt wird, gibt es dennoch in der Praxis einige Patienten, die spezifische sensorische Defizite wie taktile Wahrnehmungsstörungen als eines ihrer Hauptprobleme einschätzen [2,4] Ziel der SENSe-Studie war es, Verbesserung der funktionellen sensorischen Diskrimination zu erreichen, was bei den Patienten in der Studie eindrucksvoll gelang [6]. Jedoch ergaben sich nur sehr geringe und ebenfalls sehr heterogene Effekte auf einen besseren Armeinsatz im Alltag im Zusammenhang mit der verbesserten sensorischen Diskrimination [9].…”
unclassified